Multiple stab injuries in an infant with silent bowel perforations: a case report - C., Danny Darlington; G., Fatima Shirly Anitha (International Surgery Journal, 2018)
Penetrating injuries of the abdomen occur rarely in infants and are mostly accidental. Non-accidental injuries are very rare. We report an infant boy who was stabbed by his father, at sixteen sites all over his abdomen and chest, with a pair of scissors. The child was clinically stable on presentation but omentum was seen protruding from one of the stab wounds. There was no evidence of peritonitis and imaging was normal. The stab wounds were explored, and laparotomy was performed. Intra-operatively, there was a sealed gastric perforation, a mesenteric tear and a long ileal laceration, which were all repaired primarily. In our case, though imaging was normal, a high clinical suspicion and early laparotomy reduced the morbidity and avoided mortality. This case report emphasizes the high index of suspicion for intra-abdominal injuries needed in penetrating abdominal injuries and the need for early exploration even if imaging and clinical status dictate otherwise.